The Positive Politeness in Conversations Performed by the Students of English Study Program of Timor University - Imanuel Kamlasi (Metathesis: Journal of English Language, Literature, and Teaching, 2017)
In daily conversation, speakers tend to choose appropriate strategies to saveface. This research tends to analyze the politeness in the students’ conversation. The objectives of the research areto describe the type of address terms of positive politeness andto find out the percentages of address terms of positive politeness in students’ conversations.The method applied in this research was descriptive qualitative method. There were 26 students chosen the sabjects in this research. The data were in the script of conversationin the form of sentences, clauses or words. To obtain the data, the TVR was used. The data were analyzed through transcribing, codifying, classifying, analyzing and discussing.The result of the research shows that the address terms of positive politeness in conversation are greetings, thanking, praising, apology, congratulating, intimacy, obedience, question, request, suggestion, rejection, chastisement, and disagreement. The data in the first category shows that greetings make 27.27% of the total address terms. The thanking is 22%. The apology makes 15%; the intimacy and praising are 10%. The congratulation address is 9% and the lowest is obedience, 7.14% of the total address terms. In the second category; the question is the highest percentage which is 40%. The request is 22%, and then disagreement is 14 %. The suggestion makes 11% and the rejection makes 8%. The chastisement is the lowest percentage which is 5% of the total address terms.Keywords: positive, politeness, address terms